Studi Jaringan Aktor dalam Perumusan Kebijakan Publik - Taufik Taufik (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2017)
The formulation of network-based public policy is a new perspective in creating democratic government. Generally, network approach has been using by many countries with high level public participation. This study is aimed to explain the concept of network-based public policy formulation. In network approach, government is no longer become a single actor in formulating public policy. Government has to be able to build inter-actor network outside of government, such as professional parties, NGOs, media, interests groups and people. The existence of these parties will create network-based public policy which is not based on individual interest or some parties. Lack of resource can be solved by building inter-actor network in the process of creating public policy.